디지털 기술 교육 환경 기반 수학교육에 대한 국내 선행 연구의 경향성 분석 연구 - 고호경; 맹은경; 손복은 (East Asian Mathematical Journal, 2023)
The core of the change in the era of the 4th industrial revolution is the change in the base of ‘digital technology’. These changes are incomparably large and are expected to have a more important impact on our lives than ever before. One of the major inflection points in the transition to the digital era is the education field, and IT technology has become an essential element in the educational field. Accordingly, this study examines domestic research trends related to the educational environment based on digital technology. Then, we would like to provide implications for the establishment of a digital-based educational environment that will change in the future. To this end, Semantic network analysis has been conducted to quantitatively structure text data obtained from studies related to digital technology in the field of mathematics education over the past 10 years, and the discussion will continue based on the results.
Keywords: digital technology; education environment; text analysis; research trend